Japanese Encephalitis and Dengue Fever Co-infection - Sumaya; Kompally Varun; Kotti Ramya Sree; Saniya Mehrin (International Journal of Tropical Medicines, 2024)
Dengue virus (DENV) and Japanese encephalitis virus (JEV) are two significant pathogenic viruses that can cause severe encephalitis. Dengue and Japanese encephalitis are vector-borne illnesses.Arboviruses that are carried by mosquitoes are significant India's causes of death and morbidity The rainy season, when the vector population grows, is when both dengue and Japanese encephalitis transmissions peak. We still don't fully understand how the CNS is involved in dengue and Japanese encephalitis co-infection-associated acute encephalitis syndrome (AES), therefore understanding the etiology, treatments, clinical care, and prevention of these tropically neglected illnesses is imperative. In endemic nations, only few cases of their co-infection have been documented. However, we describe the case of a 30-year-old man who had a history of Chikungunya, fever, and hematuria in addition to Dengue (Igm + ve).following laboratory and radiographic tests that established this patient's co-infection with Dengue and JE.Enhancing surveillance and bolstering healthcare infrastructure in endemic regions are paramount to promptly recognizing and effectively managing cases of AES attributable to flavivirus coinfections. Additionally, concerted efforts to enhance vector control measures and expand vaccination coverage against Japanese encephalitis are vital components of a comprehensive strategy to mitigate the impact of these arboviral diseases on public health.
Keywords: Dengue; arboviruses; chikungunya; hematuria; japanese encephalitis